Ginger, Andrew. Instead of Modernity. The Western canon and the incorporation of the Hispanic (c. 1850-75). Manchester: Manchester University Press, 2020. - Vega, Jesusa (Anales de Historia del Arte, 2021)
Reseña de la obra de Ginger, Andrew. Instead of Modernity. The Western canon and the incorporation of the Hispanic (c. 1850-75). Manchester: Manchester University Press, 2020.